The Conditions of Coral Reef Ecosystem on Seureudong Island, South Aceh - Darmarini, Ananingtyas S; Nurul Najmi; Eka Lisdayanti; Lubis, Friyuanita (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
The coral reef ecosystem on Seureudong Island, Sawang Bau Village, Sawang District, South Aceh is very important for the surrounding ecosystem, with the fringing reef type, namely the shape of its growth around the island. This study aims to determine the current condition of coral cover and the types available on Seureudong Island. The method used is the Point Intercept Transect (PIT). The results showed that the forms of coral found at the study site were branching, digitate, encrusting, foliose, massive, mushroom, plates, and submassive. The percentage of the bottom substrate is dominated by hard coral (hard coral) at 45.3%, Dead Coral with Algae/DCA (37.11%), and (9.89%), rubble of 3.56%, rock (1.56%), algae turf (1.44%), macroalgae (1%) and dead coral (0.11%). At the study site, 25 genera were found with Porites (36%) as the most common genus found. At the research location, there are also genera with a total presence of less than 1%. These genera are Acanthastrea, Ctenactis, Favia, Favites, Fungia, Gardineroseris, Goniopora, Halimeda, Heliopora, Hydnophora, Leptastrea, Montastrea, Pavona, and Seriatopora. The quality of the waters at the research location still complies with the standards of coral life. The results of these observations must be carried out periodically so that they can always update the condition of the coral reefs on Seureudong Island